Corporate Business Strategy and Tax Avoidance Culture: Moderating Role of Gender Diversity in an Emerging Economy - Zhang, Xiaochen; Husnain, Muhammad; Yang, Hailan; Ullah, Saif; Abbas, Jaffar; Zhang, Ruilian (Frontiers in Psychology, 2022)
Tax payments stimulate business enterprises to choose tax management through tax avoidance activities, which is the legal practice to reduce the amount of tax payable. In developing economies, taxation is considered more critical to a country's budget and revenues. This paper investigates whether various business strategies influence firms' corporate tax avoidance decisions by adopting business strategies. Besides, it explores how gender diversity can ease this relationship. This study has chosen a sample of 115 organizations from Pakistan's non-financial sector. The time frame is five years, including once a year. The present model employed a generalized moment method (GMM) and tested the proposed hypothesis to draw the results. The study has taken firms' size, leverage, and business profitability as control variables. The study outcomes by using the GMM method demonstrate that the presence of female directors reduces tax avoidance behavior in prospector companies. This study provides insight into future research to stakeholders, government officials, tax authorities, and policymakers. The findings offer valuable recommendations and practical insights and implications. The findings provide future directions for research to test different frameworks to attain beneficial results to promote the responsibility of tax payment culture.